2021
DOI: 10.1186/s12891-021-04593-y
|View full text |Cite
|
Sign up to set email alerts
|

Why PRP works only on certain patients with tennis elbow? Is PDGFB gene a key for PRP therapy effectiveness? A prospective cohort study

Abstract: Background There is variability in individual response to platelet-rich plasma (PRP) therapy in tennis elbow treatment. Genetic variation, especially within genes encoding growth factors may influence the observed inter-individual differences. The purpose of this study was to identify polymorphic variants of the platelet-derived growth factor beta polypeptide gene (PDGFB) that determine an improved individual response to PRP therapy in tennis elbow patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In our previous work, we showed that specific genotypes of the PDGFB gene, namely TT (rs2285099), CC (rs2285097), and AA (rs2247128) were associated with a significantly higher effectiveness of PRP therapy. during almost the entire one-year follow-up period [ 13 ]. These data, together with the results of the present study, suggest that the body’s response to the PRP therapy may be the result of the interaction of multiple gene variants (multi-gene inheritance model).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we showed that specific genotypes of the PDGFB gene, namely TT (rs2285099), CC (rs2285097), and AA (rs2247128) were associated with a significantly higher effectiveness of PRP therapy. during almost the entire one-year follow-up period [ 13 ]. These data, together with the results of the present study, suggest that the body’s response to the PRP therapy may be the result of the interaction of multiple gene variants (multi-gene inheritance model).…”
Section: Discussionmentioning
confidence: 99%
“…The study population was the same as in our previous work [ 13 ]. Patients were recruited for the study between November 2018 and November 2019.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations